Qur’anic Interpretation of Khamr and Zina in MUI Fatwas: A Multidimensional Maqāṣid al-Sharī‘ah Analysis - Hariyadi, Muhammad; Era Elraisy, Tharekh; Nasirin, Nasirin; Nurkholilah, Siti; Syafruddin , Wahid (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study addresses two research questions: how are Qur'anic verses on khamr and zina interpreted in the fatwas of the Indonesian Council of Ulama (MUI), and to what extent do these interpretations reflect Jasser Auda's multidimensional maqāṣid al-sharī‘ah approach? This study employs a qualitative field research method using in-depth interviews with members of the MUI Fatwa Commission and document analysis of relevant MUI fatwas. The collected data were analyzed descriptively and analytically through Jasser Auda's multidimensional framework, focusing on linguistic, socio-historical, temporal, purposive, and object-related dimensions of Qur'anic interpretation. The findings demonstrate that MUI fatwas on khamr and zina substantively employ a multidimensional pattern of Qur'anic interpretation. In the case of khamr, this approach is reflected in the gradual understanding of the relevant verses, the distinction between khamr and alcohol, and the emphasis on the protection of intellect (ḥifẓ al-‘aql). In the case of zina, it is reflected in the shift from a sanction-oriented interpretation toward the protection of lineage, human dignity, and public welfare. Although MUI has not explicitly formulated its fatwa methodology within Jasser Auda's theoretical framework, its legal reasoning substantially corresponds to the multidimensional maqāṣid al-sharī‘ah approach. This study therefore contributes to strengthening maqāṣidī Qur'anic interpretation and enriches contemporary Islamic legal studies on the relationship between Qur'anic interpretation, fatwa formulation, and the objectives of Islamic law.